Evolution of the butterfly image in Portuguese lyrics: Camões and Portuguese poets of the 18th-19th centuries - Varvara A. Makhortova; Marina V. Kutyeva (RUDN Journal of Studies in Literature and Journalism)
The paper examines originality and dynamics of the butterfly image in Portuguese poetic texts of the 16th-19th centuries. This issue has not been considered before that determines the relevance and novelty of our article. The poems of L.V. de Camões, M.M. du Bocage, J. Dinis, J. de Deus are used as material. The work focuses on the problem of continuity, development and expansion of the traditional symbolism of a recurrent image steadily reproduced in world literature and metaphorically used to depict the inner personal world. Results of the study indicate that the image of butterfly in Portuguese poetry has significant specificity. The semantics of love in its most diverse manifestations comes to the fore. The traditional symbolism of “butterfly as a woman” is replaced by a stable associative parallel “butterfly as he, flower or flame as she”. The association with feelings and soul experiencing renewal (Dinish) is also relevant. The author’s parallel “zealous service and duty fulfillment” (Camões) is less conventional, but original. Thus, in Portuguese poetry, the literary semantics of the butterfly image is diverse. It is characterized by both continuity and creative increments of meaning.